Contemporary issues in apraxia of speech. Issue 4 (3rd April 2021) - Code, Chris
ABSTRACT: Background: Apraxia of speech (AOS) has been central in aphasiology for over 200 years. It has generated theoretical and clinical controversy and contributed significantly to the development of knowledge of how speech is formulated and generated by the brain. Main Contribution: This short review introduces theoretical, experimental and clinical studies concerning current issues in apraxia of speech. Conclusions: Progress in our understanding of apraxia of speech is advanced by the contemporary issues presented in the studies making up this special issue in aphasiology.